Aspectos de Validação do Método de Engenharia Reversa Fusion-RE/I aplicado a um Sistema Hipermídia - Feltrim, Valéria Delisandra; Fortes, Renata Pontin de M.; Silva, Willian Francisco da (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1999)
The growth of the software market has leading to an increasing use of development techniques, which are, sometimes, informal ones. The maintenance of such software is problematic, since its documentation rarely reflects the implemented code. In this context Reverse Engineering of Software can help by means of recovering the project information lost during the development phase and documenting the current software state. This article discusses the issues emerged during the application of the method of reverse engineering named Fusion-RE/I. The described experiment is part of the re-engineering of a prototype hypermedia system, which has, as main goal, to adapt it to a Software Engineering domain. Since the target is a hypermedia system, the results obtained during the use of Fusion-RE/I can be registered as a hyperdocument. By doing that, it is possible to observe and analyse some relevant issues concerning the method Fusion-RE/I.